α-Chymotrypsin catalyses the synthesis of methotrexate oligomers - Noro, Jennifer Martins (2020)
The enzymatic synthesis of methotrexate (MTX) catalysed by ? -chymotrypsin was studied for the first time. The proteolytic enzyme displayed activity for the synthesis of MTX oligomers composed by 6 repeating units (DPavg?=?1.5). For longer oligomers, molecular dynamics simulations confirmed that as the oligomeric chain grows its accommodation in the enzymes active site is hindered, which is evidenced by a decrease of the binding energy associated. The full characterization of the oligomers produced was performed by nuclear magnetic resonance (NMR, 1H and 13C), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF), electrospray ionization (ESI) and differential scanning calorimetry (DSC).